KELIMPAHAN DAN KEANEKARAGAMAN ARTHROPODA PERMUKAAN TANAH PADA EKOSISTEM PERTANAMAN CABAI RAWIT (CAPSICUM FRUTESCENS L.) DI KURIPAN LOMBOK BARAT - Kamila Yasurruni; Ruth Stella Petrunella Thei *2; Mery Windarningsih*3 (CROP AGRO, Scientific Journal of Agronomy, 2019)
ABSTRACT Arthropods found on the surface of the soil and plant canopy that interact with small chili plants, which act as predators, parasitoid, herbivores, scavengers, decomposers, pollinators, and pests. Diversity is a function of stability, the more diverse the arthropods in the plantation ecosystem, the more stable the ecosystem is, and vice versa. The research aims to determine the level of abundance and the diversity of soil the surface Arthropods in small chili (Capsicum frutescens L.) plantations in Kuripan West Lombok. The methods used in this research is descriptive, the observations were made using the pitfall trap when the plant age 45 days after the interval once a week for 10 observations. The finding showed that there were 7 soil surface Arthropods families of family Formicidae 25,68 %, Carabidae 20,39 %, Lycosidae 19,26 %, Araneidae 13,48 %, Oxyopidae 13,32 %, Acrididae 5,30 %, Dan Trigoniulidae 2,57 %. Soil Arthropods diversity (H’) index of 1,8 including low diversity. Keywords : Ecosystem of small chili, Arthropods.